IMPACTS OF THE USE OF PSYCHOSTIMULANTS AND BENZODIAZEPINES ON SLEEP QUALITY, MEMORY AND LEVELS OF MEDICAL STUDENTS (CIPEEX, 2026)
Introduction: The medical academic environment is characterized by intense study loads and high stress, favoring the use of substances such as psychostimulants (PSEs) and benzodiazepines (BZDs). While PSEs are used to increase wakefulness and cognitive performance, BZDs are used as anxiolytics and sleep inducers, both with potential adverse effects on mental health and academic performance. Objective: To analyze the impacts of PSE and BZD use on sleep quality, memory, and stress levels in medical students. Method: An integrative literature review was conducted in PubMed/MEDLINE, Cochrane, Scopus, and EMBASE databases. Original articles published in English, available in full, and addressing at least one of the outcomes of interest were included. Twelve cross-sectional studies were selected, totaling 2,201 medical students. Results: PSE use was associated with anxiety, insomnia, palpitations, and depressive symptoms. While BZDs alleviate anxiety and difficulty sleeping, they have been associated with memory impairment and a risk of dependence. Regarding sleep quality and stress levels, studies have shown divergent results, with no consensus on the magnitude of the effects. Conclusion: The consumption of PSE and BZDs among medical students poses a risk to physical and mental health, with potential impacts on memory, sleep, and stress management. Further research, especially randomized clinical trials, is needed to better understand the causal relationship and inform health policies targeting this population.
Keywords: Psychostimulants; Benzodiazepines; Quality of life; Medical students